2000
DOI: 10.2166/wst.2000.0507
|View full text |Cite
|
Sign up to set email alerts
|

Studies on activated sludge response to variations in the composition of a synthetic surfactant-containing feed effluent

Abstract: Laboratory batch and sequencing-batch reactors and closed respirometry techniques were used to study the response of activated sludge to non-ionic synthetic surfactants. Two laboratory-grade and three commercial surfactant mixtures used in the textile industry (alkyl- and alkylphenol-ethoxylate types) were tested. Respirometric profiles during degradation experiments were complemented with titrimetric surfactant measurements and TOC determinations, representing primary and ultimate biodegradation, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…At the same time, for anionics, the dehydrogenase activity was three or even four times lower than for nonionics at the same initial concentration of surfactant in wastewater. These results confirmed the observations made by Carvalho et al that, though nonacclimatized, the sludge was not inhibited by APE and their biodegradation products during batch and sequencing batch laboratory tests [25]. Also in the papers reviewing the fate and the ecotoxicity of the synthetic surfactants in the environment, anionics are usually believed to be more toxic than nonionics towards aquatic organisms excluding some products of APE breakdown, i.e.…”
Section: Discussionsupporting
confidence: 88%
“…At the same time, for anionics, the dehydrogenase activity was three or even four times lower than for nonionics at the same initial concentration of surfactant in wastewater. These results confirmed the observations made by Carvalho et al that, though nonacclimatized, the sludge was not inhibited by APE and their biodegradation products during batch and sequencing batch laboratory tests [25]. Also in the papers reviewing the fate and the ecotoxicity of the synthetic surfactants in the environment, anionics are usually believed to be more toxic than nonionics towards aquatic organisms excluding some products of APE breakdown, i.e.…”
Section: Discussionsupporting
confidence: 88%
“…However, at full operation (F1: 800 m 3 /day, F2: 2800 m 3 /day), HRT values would be shortened to 18 h and 9 h for F1 and F2, respectively. In that case, F1 may be still on the safe side regarding nonylphenolic removal, but F2 may be at risk in terms of complete mineralization of NPEO metabolites, as suggested by Birkett and Lester [109], Carvalho et al [123], Maki et al [125], and Petrie et al [108].…”
Section: The Role Of the Secondary Activated Sludge Processmentioning
confidence: 99%
“…Firstly, the oxidation of ethoxylate chain as primary degradation may take place as quickly as within 10 h of aeration [123,124]. The next phase as mineralization of decomposed products may consume an additional 10 h for the induction of specialized enzymes or shifts in bacterial inoculum that may degrade those substances via different mechanisms [109,123,125]. Consequently, an ultimate degradation time of about 20 h at the F/M (substrate/biomass) ratio of 0.24-0.86 is suggested by Carvalho et al [123].…”
Section: Persistence Of Np and Npeo Metabolites And The Implication Omentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work (7) has indicated the continued existence of marine pollution with alkylphenol polyethoxylates. Studies on the response of activated sludge to variations in the composition of feed effluent (8) have indicated that alkyl ethoxylateadapted biomass was more capable of adaptation to alkylphenol ethoxylate than the reverse. Overall, there are conflicting views on the fate and effect of the present class of alkylphenol polyethoxylates in the environment.…”
mentioning
confidence: 99%